Synopsis: Quantifying food losses in the beans value chain in Rwanda - Results from a baseline survey - Bachewe, Fantu Nisrane; Delgado, Luciana; Niyonsingiza, Josue (International Food Policy Research Institute, 2025)
Reducing food loss has become important, particularly in Sub-Saharan Africa, due to its direct impact on food security. Food loss also reduces producer incomes, increases food prices, and wastes natural resources, resulting in unnecessary greenhouse gas emissions. Most estimates of food loss have been heavily criticized for lacking sound methodological basis. This study uses a novel methodology to measure food loss and identify where it occurs along the beans value chain in Rwanda.